2020
DOI: 10.1002/etc.4639
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Acute Toxicity of Imidacloprid with Alternative Systemic Insecticides in the Aquatic Insect Chironomus dilutus

Abstract: Acute (96‐h) toxicities of 5 systemic insecticides (chlorantraniliprole, cyantraniliprole, flupyradifurone, flubendiamide, and sulfoxaflor) were tested on larval Chironomus dilutus and compared with the neonicotinoid imidacloprid. Three insecticides were less acutely toxic than imidacloprid (2.5–25 times lower). However, chlorantraniliprole and cyantraniliprole were 1.5 to 1.8 times more toxic to C. dilutus. Thus, these ryanodine receptor agonists could pose a higher risk to aquatic insects than their neonicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Saito et al (2014) reported that the nymphal growth of S. frequens was poorer in paddies with CAP application than without. This difference may have resulted from reduced abundance of prey organisms in rice paddies with CAP application, owing to high acute toxicity to invertebrate prey such as water fleas (e.g., Cui et al 2017;Lavtižar et al 2015) and midges (e.g., Maloney et al 2019;Rodrigues et al 2015). Likewise, Hashimoto et al (2020) showed negative effects of CAP on the abundance of some invertebrates such as sludge worms and microcrustaceans in a paddy mesocosm experiment in which CAP was applied at the same dose as here; they reported that the maximum concentration of CAP in paddy water reached 5-15 μg/L within a few days after transplantation of rice seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Saito et al (2014) reported that the nymphal growth of S. frequens was poorer in paddies with CAP application than without. This difference may have resulted from reduced abundance of prey organisms in rice paddies with CAP application, owing to high acute toxicity to invertebrate prey such as water fleas (e.g., Cui et al 2017;Lavtižar et al 2015) and midges (e.g., Maloney et al 2019;Rodrigues et al 2015). Likewise, Hashimoto et al (2020) showed negative effects of CAP on the abundance of some invertebrates such as sludge worms and microcrustaceans in a paddy mesocosm experiment in which CAP was applied at the same dose as here; they reported that the maximum concentration of CAP in paddy water reached 5-15 μg/L within a few days after transplantation of rice seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of point mutations in lepidopteran RyR that cause insecticide resistance [ 45 , 56 , 58 ]. However, recent reports have raised concerns about the adverse effects of diamide insecticides on mammals [ 6 , 9 , 28 , 32 , 34 , 39 , 48 , 61 ]. In this study, we investigated the behavioral effects, neuronal activity, and endocrinological changes in male mice after a single administration of the NOAEL level of CLO or CAP and found that CAP affects the nervous system of mice.…”
Section: Discussionmentioning
confidence: 99%
“…They are attracting attention as alternatives to organophosphorus and neonicotinoid pesticides, which have been disputed as toxic. However, CAP has been reported to cause genotoxic, behavioral, and endocrine effects in aquatic organisms and vertebrates [ 9 , 28 , 34 , 37 , 40 , 48 , 61 ], and the binding site of CAP has been identified in mammalian RyR1 [ 32 ].…”
mentioning
confidence: 99%
“…10 Although SFX was banned in France in 2020 because of its "high bee toxicity", it is still used in many countries worldwide, particularly in developing countries; its negative effects on aquatic organisms have become the subject of growing concern. 11,12 Studies showed that some metabolites are more toxic than parent compounds, including neonicotinoid pesticides. 13 For example, imidacloprid, thiamethoxam, and their metabolites accumulate substantially in the gonads of Eremias argus (Phylum chordate: Lizardales), causing endocrine damage.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish embryos exposed to SFX exhibit increased acetylcholinesterase (AchE) activity in brain and muscle tissue . Although SFX was banned in France in 2020 because of its “high bee toxicity”, it is still used in many countries worldwide, particularly in developing countries; its negative effects on aquatic organisms have become the subject of growing concern. , …”
Section: Introductionmentioning
confidence: 99%